Implementation of the General Murabahah Bil Wakalah Agreement in BMT UGT Nusantara Jajag Banyuwangi Financing Products - Sabrina Salma; Nur Anim Jauhariyah (Universitas KH. Abdul Chalim Mojokerto, 2025)
Contract murabaha as one of the instruments financing sharia, giving suitable alternative​ with principal justice and transparency in transaction finance. While that, the use of please in contract This allow institution for act as representative in management financing, so that increase flexibility services. Research This aiming to study implementation contract murabaha bil wakalah general in product financing at BMT UGT Nusantara Jajag Banyuwangi. Method research used​ is analysis qualitative with interview deep to member as well as the BMT manage. The results of the study show that implementation contract give impact positive to satisfaction members, where ease and clarity in transaction can felt by the BMT members. However, there are a number of challenges like level understanding members who are still limited about contract this and the risks that need to be taken into account managed by the institution. The conclusion of study This the need optimization socialization and education about contract murabahah bil wakalah general, and development more products​ innovative and responsive to need members, with Thus BMT UGT Nusantara Jajag English expected can strengthen his position as institution finance micro effective and reliable sharia.​